Ensuring the Long-Term Provision of Heathland Ecosystem Services—The Importance of a Functional Perspective in Management Decision Frameworks - Walmsley, David C.; Delory, Benjamin M.; Alonso, Isabel; Temperton, Vicky M.; Härdtle, Werner (Frontiers in Ecology and Evolution, 2021)
The ecosystem services framework can be used as a way of balancing economic, ecological and societal drivers in land management decision-making processes. As heathland management is typically linked directly to services, the aim of this study was to quantify trade-offs related to the effects of five common heathland management measures (grazing, mowing, burning, choppering and sod-cutting) using quantitative data from empirical studies within a North-western heathland in Germany. Besides important services (groundwater recharge and quality, carbon stocks and appreciation by the general public) we included ecosystem functions (balances of nitrogen, phosphorus and major cations) and the net cost of management implementation as trade-off components. We found that all management practices have advantages and disadvantages leading to unavoidable trade-offs. The effect of a management practice on the trade-off components was often closely related to the amount of biomass and/or soil removed during a management cycle (Rannual). Choppering and sod-cutting (large Rannual by involving soil removal) were very good at maintaining a low N system whilst concurrently increasing groundwater recharge, albeit at the cost of all other components considered. If the aim is to preserve heathlands and their associated ecosystem services in the long-term this trade-off is inevitable, as currently only these high-intensity measures are capable of removing enough nitrogen from the system to prevent the transition to non-heather dominated habitat types. Our study, therefore, shows that in order to maintain structural integrity and thereby the service potential a habitat provides, management decision frameworks may need to prioritize ecosystem functioning over ecosystem services. Burning and mowing (low Rannual) were best at retaining phosphorus, cations and carbon and had the lowest costs. Grazing (intermediate Rannual) provided the highest relative benefit in terms of groundwater quality and appreciation. Together these results can help identify management combinations in both space and time, which will be more beneficial for functions and services than management practices considered in isolation. Furthermore, our study assists in recognizing key areas of action for the development of novel management practices and can help raise awareness of the diversity of rare species and potential benefits to people that protected cultural landscapes provide.